DETERMINATION THE PREVALENCE AND ANTIMICROBIAL SUSCEPTIBILITY OF BACTERIA ISOLATED FROM BURNS AND WOUNDS - Marwah K. Khudhair,; Mouruj A. AlAubydi, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The current study conducted to identify the bacterial isolates from burns and wound infections that are responsible for various skin complication in such conditions and determination the development of antimicrobial resistance among these bacterial isolates. This study is carried out Between September 2020 to December 2020, a total number of (103) burns and wound swabs were taken from different patients from different hospitals in Baghdad city, the specimens were collected from; burns (57) and wound (46) swabs, the specimens were included; (51) female and (52) Male, the age average between (2 - 70 years). The positive bacterial containing specimens are (93) swabs, most of them are mixed (82 specimens) with different types of bacterial species and only (11 specimens) are contained with one type of bacterial isolate, while the negative bacterial containing are (10) swabs that showed no aerobic bacterial growth.. Staphylococcus sp. is recorded the most prevalence organisms found in wounds and burns 75/163(46%) included 31(41.3%) and 44(58.7%) isolated from burns and wounds respectively. Whereas Enterobacteriaceae sp. revealed that 57/163 ( 35%), 25(44%) from wounds and 32(56%) from burns. Also Pseudomonas sp. 23/163( 14.1%), Acinetobacter sp. 5/163(3.1%), and Corynebacterium sp. 3/163(1.8%) were isolated from infected wound in a percentage (47.8%,60%,and 33.3%) and from burns (52.2%, 40% and 66.7%) respectively. Another experiment was performed to measure the antimicrobial susceptibility against several antimicrobial agents included; Methicillin, Caphalothin, Tobramycin, Azithromycin, Bacitracin, Novobiocin, Levofloxacin and Sulfamethoxazole + Trimethoprim. The results showed increasing the resistance percentages among different bacterial isolates, and developed multidrug resistant bacteria.